Risks-based Stand Normality for Sustainable Yield Forest Plantation in Perum Perhutani - Rohman Rohman; Sofyan P Warsito; Ris Hadi Purwanto; Nunuk Supriyatno (Jurnal Ilmu Kehutanan)
In any situation, either secure or insecure, teak forest plantations encounter high risks due to ecological and social disturbances, causing degradation and decrease their normality in terms of areas and standing stock. This research aimed to determine the normality standard of teak forest plantations under risks as a basis for better sustained yield regulation. This research was conducted in forest management unit (FMU) of Randublatung, state-owned forest company (Perhutani), located at Central Java. The risk of forest damages, called casualty per cent, was calculated using a series of age class structures based on a 10-year periodic forest inventory for four sequential planning periods:1983/1992, 1993/2002, 2003/2012,to 2013/2022. The normal forest was determined based on the stands area basis, which was defined based on the final cutting area that already incorporates casualty per cent, in such a way that each year the newly planted forests areas have relatively the same number. The results showed that without casualty per cent, the normal forest built every year in FMU Randublatung was 456 ha/year for a 60-year rotation cycle. However, by incorporating the damage risks (casualty per cent), the normal forest area in KPH Randublatung should be built only 229.5 ha/year or just 50.3% of the current planning. Furthermore, in order to obtain this annual harvesting, the normal forests should have age classes structures from age class I, II, III, IV, V, and VI, in such a way that their areas equal to 6,875 ha, 5,784 ha, 4,711 ha, 3,997 ha, 3,232 ha, and 2,761 ha, respectively.